The determination of the thermal reliability criterion for building envelope structures - Farenyuk, Gennadiy (Array, 2019)
The paper presents the basic methodical principles for the time analysis of the variations of envelope structures’ thermal insulation properties and for the substantiation of the thermal reliability criterion, which should allow the analysis of the actual parameters of heat losses during the operation of buildings. In the paper, the state of the envelope structures thermal failure, the concept of building thermal envelope thermal reliability and the principles of its rating are defined. The physical meaning and basic criterion of the envelope structure thermal reliability are formulated. The application of the thermal reliability criterion allows determining the probable variations in the thermal insulation properties during the building operation and, accordingly, the changes of the building energy performance over time.